Provincial international migration distribution in Spain: which factors are behind? - Jose Villaverde; Adolfo Maza; María Hierro (European Regional Science Association (ERSA), 2011)
International migration issues are at the forefront of the political debate in the European Union (EU). Some reasons justify the increasing relevance of this topic, being the unprecedented scale of international migration flows, especially in countries such as Spain, the most prominent. In fact, adequate responses to the necessity for controlling effectively large flows of irregular immigration, and also safeguarding the internal security, are insistently demanded and always placed in the center of the political debate. Thus, recent studies portraying immigration experiences in the EU have been prolific in the literature on international migration. Some of these were applied to Spain as a representative country of changes in international migration patterns. However, and although some contributions to the analysis of international migration in Spain have been made, an examination of the international migration distribution (IMD) is still a pending question that needs further analysis. Accordingly, the aim of this paper is to analyse some relevant aspects on IMD in Spain at regional level. After a descriptive analysis showing the importance that international migration plays in today's Spanish demography and economy, the paper examines the IMD's external shape and its intra-distribution mobility. Subsequently, an analysis of the factors that might be behind the IMD and its dynamics is carried out. The results will give information about the role played by factors such as geographical location, per capita income, industry mix, employment density and social networks in explaining this issue.
Keywords: 330; international migration; Spanish regions; distribution dynamics; highest density regions